Classroom Management Strategies in English Language Teaching: A Perspective of English Teacher - Rifdah Diniatulhaq; Annafi Ananda Oktaria; Azwar Abbas (Universitas Sulawesi Barat, 2020)
The essence of classroom management is the creation of more conducive student learning conditions. The conducive learning conditions are the most important prerequisite for the smooth implementation of student learning activities, so that the smooth learning process influences the learning outcomes more optimally. Good class management is one that can serve and help students' needs in learning. Therefore, the characteristics and needs of students are the first things that need to be known and taken into account by the teacher as well as possible. To collect the data, the researchers used semi-structure interview and the obtained data were analyzed with descriptive-qualitative method.The result showed that there are three dominant aspects of classroom management system, namely; curriculum and instructional management’s (i.e. curriculum planning, making the lesson plan, scheduling, method implementation learning and assessment), management behavior (i.e. teacher sets and enforces the rules and the procedure, teacher starts the lesson, teacher builds relationships with students, teachers apply discipline and consequences and teacher is involved in the process learning), and management of the environment (i.e. class settings namely structuring furniture and determining the number of students).